2014
DOI: 10.1039/c4nr00254g
|View full text |Cite
|
Sign up to set email alerts
|

One-step growth of triangular silver nanoplates with predictable sizes on a large scale

Abstract: A one-step growth of triangular silver nanoplates on a large scale is developed by a coordination-based kinetically controlled seeded growth method, with their edge length precisely tuned from 150 nm to 1.5 μm, and surface plasmon resonance extends to full near-infrared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 27 publications
0
74
0
Order By: Relevance
“…AgNPLs with tunable size and uniform shape can be synthesized via seeded growth method 2629 , however, the stability of AgNPLs in the polymer matrix is a challenging due to oxidation by surfactant-assisted etching. Ag@Au NPLs obtained by epitaxial growth of a layer of gold on silver can enhance their stability.…”
Section: Resultsmentioning
confidence: 99%
“…AgNPLs with tunable size and uniform shape can be synthesized via seeded growth method 2629 , however, the stability of AgNPLs in the polymer matrix is a challenging due to oxidation by surfactant-assisted etching. Ag@Au NPLs obtained by epitaxial growth of a layer of gold on silver can enhance their stability.…”
Section: Resultsmentioning
confidence: 99%
“…Also, various shape-controlled Ag nanostructures including quasispheres [43], decahedrons [44], cubes [45], prisms [46], rods [47], wires [48], tubes [49], branches [50], sheets [51], plates [52] and belts [53] have been reported. However, to the best of our knowledge, there is no report concerned with AgNPs synthesis based on solid state reactions at ambient temperature so far.…”
Section: Q3mentioning
confidence: 99%
“…Under the same amount of ingredient for crystals to grow, the more seeds concentration indicates the more nucleation sites and the shorter size of the nanocrystals [31]. A relationship between the edge length (L) and the volume of the seeds solution (V), L 2.437 = kV −1 (k is a constant), was summarized in Liu's work [24]. The shape evolution probably derived from the fact that the vertex atoms of the nanotriangles are more labile than other surface atoms, and they will migrate to the sides of the triangle to lower the surface energy [32].…”
Section: Nanotriangles Characterizationmentioning
confidence: 99%
“…For the past decade, many authors reported the solution-phase methods for preparing the silver nanotriangles [18][19][20][21][22][23][24][25][26]. One of the most often used methods is the production of silver nanotriangles from Ag + salts solution by exposure to UV-vis radiation or via chemical reduction.…”
Section: Introductionmentioning
confidence: 99%